Effect of visual condition on performance of balance-related tasks in elite dance students - Coker, E.; Kaminski T. (Motor control, 2020)
The purpose of this study was to investigate the effects of visual condition (low light, full light, and full light with mirror) on balance control and technical form during two technical dance movements in a group of elite collegiate dance students. Dancers demonstrated higher center of pressure velocity indicating lower control while performing a static dance task (parallel relevé retiré) and a dynamic dance task (fondu relevé en croix) under low light conditions than either lighted condition. Measures of Western ballet technique (pelvic obliquity, knee extension, and ankle plantar flexion) showed no decrement under low light conditions. No effect of concurrent mirror feedback was found on either center of pressure velocity or technical requirements of the dance tasks.